Human anti-rabies care in the State of São Paulo: evaluating prophylaxis conduct in individuals attacked by dogs and cats - Andrade, Bruno Fonseca Martins da Costa [UNESP] (2024)
Background: Rabies is a zoonosis usually transmitted to mammals via contact between the saliva of infected animals and either the skin or mucosa of the attacked individual, and post-exposure prophylaxis (PEP) is the only way to avoid the disease. This study aimed to perform a descriptive analysis of PEP after attacks by dogs and cats in the state of São Paulo. Methods: We analyzed the disease compulsory notification forms Human Anti-Rabies Care (CID10: W64), available in the Notifiable Diseases Information System (SINAN), from 2013 to 2017. Treatment adequacy was analyzed according to the parameters established by the Brazilian Health Ministry. Results: A total of 572,889 notifications were reported during the study period, 94.1% (538,975) of which corresponded to dog or cat attacks, with an occurrence of 26.9 cases per 10,000 inhabitants. Among the recommended procedures, the most frequent was the observation of the animals for 10 days (44.4%), which was adopted inappropriately at a lower frequency. Prophylactic conduct was adequate in 68.8% of the cases, but only 55.5% of the individuals received adequate treatment. More than 112 thousand individuals (31,4%) received a correct recommendation for PEP but did not receive adequate treatment, leading to 246,787 doses of the vaccine and 8,888 doses of rabies immunoglobulin administered without following the recommendations of the Ministry of Health. Conclusions: The use of immunobiologicals is excessive, indicating the need for investment in training health professionals to follow the recommendations of the Ministry of Health.